Integrating hydrologic modeling web services with online data sharing to prepare, store, and execute hydrologic models. (August 2020) - Gan, Tian; Tarboton, David G.; Dash, Pabitra; Gichamo, Tseganeh Z.; Horsburgh, Jeffery S.
Abstract: Web based applications, web services, and online data and model sharing technology are becoming increasingly available to support hydrologic research. This promises benefits in terms of collaboration, computer platform independence, and reproducibility of modeling workflows and results. In this research, we designed an approach that integrates hydrologic modeling web services with an online data sharing system to support web-based simulation for hydrologic models. We used this approach to integrate example systems as a case study to support reproducible snowmelt modeling for a test watershed in the Colorado River Basin, USA. We demonstrated that this approach enabled users to work within an online environment to create, describe, share, discover, repeat, modify, and analyze the modeling work. This approach encourages collaboration and improves research reproducibility. It can also be adopted or adapted to integrate other hydrologic modeling web services with data sharing systems for different hydrologic models. Highlights: An approach was developed to integrate open source cyberinfrastructure systems. Hydrologic modeling web services were integrated with a data sharing system. System integration supported web-based simulation of a snowmelt model. A browser-based user interface was implemented for modeling web services. Modeling results can be automatically shared to support reproducible research.